Freight futures: The potential impact of road freight on climate policy. (August 2017) - Carrara, Samuel; Longden, Thomas
Highlights: Road freight is a challenge for the decarbonisation of the global economy. Notable decarbonisation is likely to take place only in the second part of the century. Notable changes to fleet composition only occurs when a strong mitigation policy is implemented. The sector decarbonises by a lower extent than the rest of the economy. Low sensitivity to GDP growth is found in terms of fleet composition and fuel mix. Abstract: This paper describes changes to the modelling of the transport sector in the WITCH (World Induced Technical Change Hybrid) model to incorporate road freight and account for the intensity of freight with respect to GDP. Modelling freight demand based on the intensity of freight with respect to GDP allows for a focus on the importance of road freight with respect to the cost-effective achievement of climate policy targets. These climate policy targets are explored using different GDP pathways between 2005 and 2100, which are sourced from the Shared Socioeconomic Pathways (SSPs) database. Our modelling shows that the decarbonisation of the freight sector tends to occur in the second part of the century and that the sector decarbonises by a lower extent than the rest of the economy. Decarbonising road freight on a global scale remains a challenge even when notable progress in biofuels and electric vehicles has been accounted for.